Experts’ Validation of the Developed 3-Dimensional Automated Model of the Human Heart to Teach A Biology Concept in Ilorin, Nigeria - Olumorin, Charles Olabode; Babalola, Ebenezer Omolafe; Aladesusi, Gboyega Ayodeji; Issa, Ahmed Idris; Omolafe, Eyiyemi Veronica (Indonesian Journal of Multidiciplinary Research, 2021)
To ascertain the accuracy and usability of the instructional model, it must be verified by a professional or expert in the area of the subject content. The automated model of the human heart (3-DAMHH) has to be inspected and verified by a qualified biology education expert to ascertain its accuracy while the usability has to be verified by an educational technology expert. Hence, it is needed to determine the experts’ validation of 3-DAMHH to teach a Biology concept in Ilorin, Nigeria. Two instruments were developed: Educational Technology Experts’ Rating Scale and Biology Education Experts’ Rating Scale. Percentage scores were used to answer research questions. Findings of this study revealed the percentage score of the rating for the validation of the 3-DAMHH by the experts satisfied the required standard in the field of Educational Technology. Percentage score of the rating for the validation of the 3-DAMHH by the experts satisfied the required standard in the field of Biology. This study concluded that the developed 3-DAMHH can be used to enhanced Biology students’ performance on the topic structure of the human heart. It was recommended among others that content specialists' and experts’ validation reports should be properly followed towards developing a standard instructional media.